PENGARUH EDUKASI TERHADAP PENGETAHUAN DAN SIKAP ORANG TUA PADA KASUS SEDIAAN SIRUP OBAT PENURUN DEMAM DI DUA DESA KABUPATEN TANGERANG - Insani, Nurul; Aziya, Hasna; R, Asti Yunia; Kholifah, Eva (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2024)
Education is an educator's effort to convey knowledge or messages to communities, groups or individuals, from not knowing to knowing. Ethylene glycol and Diethylene glycol are alcohols that have toxic properties that can increase mortality and morbidity when their use exceeds the provisions or limits that have been set. This study aims to determine the level of knowledge and attitudes of parents in Kronjo Village and Bakung Village about the case of fever-reducing syrup preparations as the main factor causing atypical progressive acute renal failure in children after being given education. Cross sectional research design with pretest and posttest data collection techniques on parents in Kronjo Village and Bakung Village. The data were then analyzed using an application called SPSS (Kolmogorov-smirnov two sample test and Wilcoxon Sign Rank Test). The results showed that the level of knowledge and attitude of parents in Kronjo Village and Bakung Village had increased after being given education. This is evidenced by the results of data that has been analyzed using the Wilcoxon Sign Rank Test with a p value of 0.000 ≤ 0.05, which means there is a significant difference.